2018
DOI: 10.1158/0008-5472.can-17-3973
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Priming of Adoptively Transferred T Cells with a RORγ Agonist Confers Durable Memory and Stemness In Vivo

Abstract: Adoptive T-cell transfer therapy is an FDA-approved treatment for leukemia that relies on the ex vivo expansion and reinfusion of a patient’s immune cells, which can be engineered with a chimeric antigen receptor (CAR) for more efficient tumor recognition. Type 17 T cells, controlled transcriptionally by RORγ, have been reported to mediate potent antitumor effects superior to those observed with conventionally expanded T cells. Here, we demonstrate that addition of a synthetic, small-molecule RORγ agonist duri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 31 publications
5
33
0
Order By: Relevance
“…Our data demonstrated that HDAC6‐depleted T H 17 cells activated IFN‐γ and granzyme B signaling in the HCC microenvironment and improved survival rate. This phenotype greatly supported a recent study which demonstrated that RoRγt agonist could potentiate adoptively transferred T‐cell therapy . Furthermore, because IFN‐γ could augment PD‐L1 to weaken tumor immune surveillance and a clinical case suggests that IL‐17A potentiates the effect of immune checkpoint therapy, we found the combination treatment by targeting HDAC6 and PD‐1 antagonist effectively eliminated advanced HCC, which partially relied on IL‐17A.…”
Section: Discussionsupporting
confidence: 87%
“…Our data demonstrated that HDAC6‐depleted T H 17 cells activated IFN‐γ and granzyme B signaling in the HCC microenvironment and improved survival rate. This phenotype greatly supported a recent study which demonstrated that RoRγt agonist could potentiate adoptively transferred T‐cell therapy . Furthermore, because IFN‐γ could augment PD‐L1 to weaken tumor immune surveillance and a clinical case suggests that IL‐17A potentiates the effect of immune checkpoint therapy, we found the combination treatment by targeting HDAC6 and PD‐1 antagonist effectively eliminated advanced HCC, which partially relied on IL‐17A.…”
Section: Discussionsupporting
confidence: 87%
“…Alternatively, Th17 cells could be transformed into Treg cells, which exert immunosuppressive effects and weaken anti-tumor immunity [46]. Paradoxically, some studies have found that Th17 cells act as tumor suppressors [47,48]. In the current study, DHA treatment significantly decreased the expression of ROR-gt and phosphorylation of STAT3 ( Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Overexpression of RORγ and RORγt can lead to obesity-associated insulin resistance and multiple autoimmune diseases such as multiple sclerosis, rheumatoid arthritis, Crohn's disease and psoriasis. On the other hand, high RORγt activity can sometimes be beneficial and has been shown to enhance antitumor immunity by increasing IL-17, GM-CSF (granulocyte-macrophage colony-stimulating factor) secretion and decreasing PD-1 expression [4,5]. The pathological functions and the therapeutic potential of RORγ make it an intriguing drug target.…”
Section: Introductionmentioning
confidence: 99%